Social networks for collaborative water management: a methodological approach to addressing wicked environmental problems - Anson, Alison A., author; Cross, Jennifer E., advisor; Goemans, Christopher G., committee member; Taylor, Peter L., committee member (Colorado State University. Libraries, 2017)
Lake pollution caused by human activity on nearby land is currently seen as one of the most pressing issues facing fresh bodies of water worldwide and particularly in the Midwestern United States. In Menomonie, a small lake-shore town in Wisconsin, lake pollution from phosphorus eutrophication has become an unhealthy nuisance for the residents that reside there. Eutrophication is the build-up of algae in waterways when there are too many nutrients, such as phosphorus, concentrated in the water. Attempts have been made by government officials, practitioners, researchers, and community members to clean up the lake or tackle the root of its cause with limited success. This research argues that this "wicked" pollution problem, while environmental and scientific in nature, cannot be resolved without a much more thorough analysis of the social aspects involved in decision-making and collaborative knowledge acquisition. I conducted a mixed methods study using interviews, digital surveys, and Social Network Analysis (SNA) of the community in question to reveal how network structure, network interactions, and actor characteristics play a role in this community's collaborative effort to address lake pollution. The following research shows that SNA, alongside qualitative field study, can reveal significant findings about the network and the environmental problem.
Keywords: lake; pollution; farmers; social; networks